2015
DOI: 10.1016/j.stemcr.2015.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Acts on Two Different Molecular Pathways to Enhance Adult Neural Precursor Proliferation/Self-Renewal and Differentiation

Abstract: SummaryThe recruitment of endogenous adult neural stem cells for brain repair is a promising regenerative therapeutic strategy. This strategy involves stimulation of multiple stages of adult neural stem cell development, including proliferation, self-renewal, and differentiation. Currently, there is a lack of a single therapeutic approach that can act on these multiple stages of adult neural stem cell development to enhance neural regeneration. Here we show that metformin, an FDA-approved diabetes drug, promot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
80
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 102 publications
(86 citation statements)
references
References 20 publications
(36 reference statements)
3
80
0
3
Order By: Relevance
“…In our study, metformin reduced apoptosis induced by SE to a greater extent than salubrinal or GSK2656157, despite the similar reductions in CHOP levels in all of the treatment groups. Although both salubrinal and metformin have neuroprotective effects, it has been reported that metformin also has the capability to enhance the proliferation of neural precursors through TAp73 [31], which may result in fewer apoptotic cells after metformin compared to the salubrinal or GSK2656157 treatment. Further studies are necessary to examine the mechanism by which metformin ameliorates apoptosis induced by SE.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, metformin reduced apoptosis induced by SE to a greater extent than salubrinal or GSK2656157, despite the similar reductions in CHOP levels in all of the treatment groups. Although both salubrinal and metformin have neuroprotective effects, it has been reported that metformin also has the capability to enhance the proliferation of neural precursors through TAp73 [31], which may result in fewer apoptotic cells after metformin compared to the salubrinal or GSK2656157 treatment. Further studies are necessary to examine the mechanism by which metformin ameliorates apoptosis induced by SE.…”
Section: Discussionmentioning
confidence: 99%
“…These events include the amyloid deposition in the brain due to the uncontrolled cleavage of APP and the degeneration of neurotoxic Aβ-42 peptides, hyperphosporhylation of tau protein and the formation of intracellular neurofibrillary tangles, the deficiency of acetylcholine (ACh) due to its increased hydrolysis by acetylcholinesterase (AChE), oxidative stress, and mitochondrial dysfunction Fouad Bulletin of the National Research Centre (2019) 43:52 (Gage 2002) and can be obtained from fetal and postmortem neonatal brain tissues (Martínez-Morales et al 2013) or differentiated from iPSCs and ESCs (Hermann and Storch 2013;Yu et al 2013aYu et al , 2013b. The mechanistic action of NSCs is regulated by metabolic processes such as oxygen consumption and energy production (Almeida and Vieira 2017;Fatt et al 2015;Wang et al 2012a). Mitochondrial dysfunction is implicated in AD progression (Swerdlow et al 2014); therefore, more research is required to estimate the connection between the metabolic switch of NSCs and AD pathogenesis (Fang et al 2018).…”
Section: Stem Cell-based Therapy For Admentioning
confidence: 99%
“…The functional role of AMPK in neuron and glial cells has been intensively studied, and it has been identified that the AMPK may affect neuronal differentiation and synaptic connectivity (Fatt et al, ). Aberrant activity of AMPK in the nervous system is associated with the neurodegenerative diseases, for example ALS, Alzheimer's disease, Parkinson's disease, and Huntington's disease (Hang, Thundyil, & Lim, ; Ju et al, ; Vingtdeux et al, ).…”
Section: Discussionmentioning
confidence: 99%